Early repolarization pattern in an ethnically diverse population: Increased risk in Hispanics. Issue 1 (22nd December 2019) - Leiderman, Ephraim; Kargoli, Faraj; Shulman, Eric; Aagaard, Philip; Hoch, Ethan; Zaremski, Lynn; Di Biase, Luigi; Kim, Soo G.; Gross, Jay N.; Ferrick, Kevin J.; Fisher, John; Krumerman, Andrew
Abstract: Background: Early repolarization (ER) pattern on ECG is associated with an increased mortality in Caucasians. This study analyzed the association between ER pattern and all‐cause mortality in a population of multiple ethnicities. Methods: A total of 20 000 individuals were randomly selected and their ECGs were analyzed for ER pattern using the 2015 consensus: end‐QRS notching or slurring with a J‐point ( Jp ) ≥0.1 mV in contiguous inferior or lateral leads. Exclusion criteria were age <18, QRS duration of ≥120 ms, and acute myocardial infarction. Kaplan‐Meier survival curves were used to assess crude survival, and multivariable logistic regression models were used to determine predictors of all‐cause mortality. Results: A total of 17 901 patients with a mean age of 53 met inclusion criteria. Individuals were 62% female, 14% White, 37% Black, 40% Hispanic, and 9% other. Median follow‐up time was 6.4 years. ER pattern was noted in 995 (5.6%) patients. Jp ≥2 mm was noted in 282 (1.6%) patients. In those with ER pattern and Jp  ≥1 mm, there was no difference in mortality when compared to individuals without Jp elevation (odds ratio [OR]: 0.962, 95% confidence of interval [CI]: 0.819‐1.131). Patients with Jp ≥2 mm had a significantly increased all‐cause mortality (OR: 1.333, 95% CI: 1.009‐1.742). This increased mortality was also significant in Hispanic patients with Jp ≥2 mm (OR: 1.584, 95% CI: 1.003‐2.502). Conclusion: ER pattern with Jp ≥2 mm is associated with increased mortality in a multiethnic population, apparently driven by an increased risk in Hispanics.